2021
DOI: 10.34119/bjhrv4n3-169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ultra-processed foods on dietary micronutrient content in patients with cardiovascular disease / Impacto de alimentos ultraprocessados sobre o teor de micronutrientes da dieta de pacientes com doença cardiovascular

Abstract: Background: Cardiovascular diseases (CVDs) are a global public health problem. Dietary patterns can modulate different aspects of the atherosclerotic process and cardiovascular risk factors. The analysis of ultra-processed foods (UPF) consumption has been an important indicator of diet quality. Objective: The aim of this study was to evaluate food intake according to levels of processing and investigate the association between UPF consumption and dietary inadequacy in patients with coronary artery disease. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Um estudo recente realizado no Brasil que incluiu pessoas com DCV, mostrou um alto consumo de alimentos ultraprocessados por esta população, isto é, de formulações industriais feitas inteiramente ou majoritariamente de substâncias extraídas de alimentos ou sintetizadas em laboratório. Este comportamento impactou, então, em ingestão inadequada de micronutrientes sendo recomendadas intervenções focadas na promoção de padrões alimentares mais saudáveis, manutenção do peso e estilo de vida saudável, tamanha importância do controle desses fatores para evitar a progressão dessas doenças (BARROSSO et al, 2021;LIMA et al, 2021).…”
unclassified
“…Um estudo recente realizado no Brasil que incluiu pessoas com DCV, mostrou um alto consumo de alimentos ultraprocessados por esta população, isto é, de formulações industriais feitas inteiramente ou majoritariamente de substâncias extraídas de alimentos ou sintetizadas em laboratório. Este comportamento impactou, então, em ingestão inadequada de micronutrientes sendo recomendadas intervenções focadas na promoção de padrões alimentares mais saudáveis, manutenção do peso e estilo de vida saudável, tamanha importância do controle desses fatores para evitar a progressão dessas doenças (BARROSSO et al, 2021;LIMA et al, 2021).…”
unclassified
“…The cross-sectional study revealed that a higher consumption of ultra-processed foods was associated with a lower intake of essential micronutrients, potentially contributing to the development and progression of cardiovascular diseases. 6 Thus, the avoidance of ultra-processed foods is the "golden rule" of national dietary guidelines recently issued in Latin American countries. 7 Even with this range of evidence discouraging the consumption of ultra-processed foods, however, these foods had played a key role during the COVID-19 pandemic.…”
mentioning
confidence: 99%